Administration of 75 mg of aspirin daily for 28 days is sufficient prophylaxis against renal transplant vein thrombosis. - Stechman, M; Charlwood, N; Gray, D; Handa, A (2007)
INTRODUCTION: Early postoperative renal transplant vein thrombosis results in graft loss. We evaluate the effect of administering aspirin 75 mg daily for 28 days following transplantation. METHODS: Prospectively collected data on the outcome of all transplants undertaken in our unit in the five-year period from January 1997 to January 2002 were reviewed, and in cases of graft failure before three months the cause was defined. RESULTS: In the study period, a total of 401 transplants were undertaken (311 cadaveric and 90 living related). There was one case of renal transplant vein thrombosis (0.25%). This represents a significant reduction on the unit's historical incidence of 5.8%, P < 0.001. CONCLUSION: Aspirin 75 mg daily is adequate to virtually abolish renal transplant vein thrombosis and has a role in thromboprophylaxis in other situations where heparin is contraindicated.